Somatic DNA demethylation generates tissue-specific methylation states and impacts flowering time. Issue 4 (25th December 2021) - Williams, Ben P; Bechen, Lindsey L; Pohlmann, Deborah A; Gehring, Mary
Abstract: Cytosine methylation is a reversible epigenetic modification of DNA. In plants, removal of cytosine methylation is accomplished by the four members of the DEMETER (DME) family of 5-methylcytosine DNA glycosylases, named DME, DEMETER-LIKE2 (DML2), DML3, and REPRESSOR OF SILENCING1 (ROS1) in Arabidopsis thaliana . Demethylation by DME is critical for seed development, preventing experiments to determine the function of the entire gene family in somatic tissues by mutant analysis. Here, we bypassed the reproductive defects of dme mutants to create somatic quadruple homozygous mutants of the entire DME family. dme ; ros1 ; dml2 ; and dml3 ( drdd ) leaves exhibit hypermethylated regions compared with wild-type leaves and rdd triple mutants, indicating functional redundancy among all four demethylases. Targets of demethylation include regions co-targeted by RNA-directed DNA methylation and, surprisingly, CG gene body methylation, indicating dynamic methylation at these less-understood sites. Additionally, many tissue-specific methylation differences are absent in drdd, suggesting a role for active demethylation in generating divergent epigenetic states across wild-type tissues. Furthermore, drdd plants display an early flowering phenotype, which involves 5′-hypermethylation and transcriptional down-regulation of FLOWERING LOCUS C . Active DNA demethylation is therefore required for proper methylation across somatic tissues and defines the epigenetic landscape of intergenic and coding regions. Abstract : Analysis of a mutant null for all four DNA demethylases in Arabidopsis vegetative tissues expands our understanding of the targets and function of DNA demethylation.